1976
DOI: 10.1139/e76-037
|View full text |Cite
|
Sign up to set email alerts
|

Magnetite–apatite intrusions and calc-alkaline magmatism, Camsell River, N.W.T.

Abstract: The Camsell River area comprises a roof pendant of volcanic rocks within an Aphebian (~1800 m.y.) orogenic belt. Magnetite–apatite intrusions and related bodies are common and are closely associated with plutons of intermediate composition. The magnetitic intrusions are interpreted as immiscible liquids that separated from a magma of intermediate composition. The immiscible fractions were predominantly crystalline when they reached their present higher levels, and final emplacement was facilitated by volatile-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…Iron oxide copper-gold styles of mineralization and IOA ± actinolite mineralization are recognized throughout the Great Bear magmatic zone, where they are spatially and temporally related to one another and extensive magmatism (Badham and Morton, 1976;Hildebrand, 1986;Gandhi, 1994;Goad et al, 2000;Mumin et al, 2007Mumin et al, , 2010Corriveau et al, 2010a, b;Potter et al, 2013;Somarin and Mumin, 2014;Acosta-Góngora et al, 2014, 2015a accepted with revisions; Mumin, 2015). We present a large-scale overview of the Great Bear magmatic zone and its geodynamic setting.…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
See 3 more Smart Citations
“…Iron oxide copper-gold styles of mineralization and IOA ± actinolite mineralization are recognized throughout the Great Bear magmatic zone, where they are spatially and temporally related to one another and extensive magmatism (Badham and Morton, 1976;Hildebrand, 1986;Gandhi, 1994;Goad et al, 2000;Mumin et al, 2007Mumin et al, , 2010Corriveau et al, 2010a, b;Potter et al, 2013;Somarin and Mumin, 2014;Acosta-Góngora et al, 2014, 2015a accepted with revisions; Mumin, 2015). We present a large-scale overview of the Great Bear magmatic zone and its geodynamic setting.…”
Section: Accepted M Manuscriptmentioning
confidence: 93%
“…3; Ootes et al, 2010;Acosta-Góngora et al, 2015b;Montreuil et al, 2013Montreuil et al, , 2016. The IOA mineralization is related to fractionation of intermediate, high-level plutons (Badham and Morton, 1976;Hildebrand, 1986;Reardon, 1992). A link between IOCG mineralization and magmatichydrothermal processes is readily apparent from the regional and detailed geological relationships (e.g., Gandhi 1994;Mumin et al 2014), but is also clearly demonstrated using   S values of the mineralization ( Fig.…”
Section: Iocg and Ioa Depositsmentioning
confidence: 99%
See 2 more Smart Citations
“…lèiifi'f». Canada (Badham et Morton, 1976 ;Hildebrand, 1986). Cependant, l'association la plus commune pour les nelsonites est avec les massifs anorthositiques.…”
Section: Model De Cimon 1998unclassified